Detection of the early putative biofilm marker pgaB among the MDR strains of A.baumannii - Navya Khanna; Smiline Girija A.S; Vijayashree Priyadharsini J (Heliyon, 2024)
Background: pgaB associated biofilm formation in Acinetobacter baumannii enhances the virulence in concert with the high propensity of drug resistance. This research is thus aimed to characterize the pgaB gene molecularly and to examine its co-occurrence with MDR. Methodology: MDR strains of A. baumannii (N = 73) were selected to detect the formation of biofilms. Genomic DNA was extracted further and screened for pgaB followed by amplicon sequencing from the representative strains. Frequency of its distribution in different groups of drug resistant strains at a significant p-value of <0.05 was further checked. Results: The biofilm assay showed high, low and negative biofilm formers in 58.9%, 31.5% and 0.9% of the strains respectively. The pgaB gene was detected in 14 strains of MDR A. baumannii (19.17%). Co-occurrence of pgaB gene was seen in all the strains that showed resistance to β-lactam inhibitors, cephems, carbapenems, fluoroquinolones and folates followed by 96% for the aminoglycosides and 25% in the efflux pump groups. Conclusion: The study findings showed the occurrence of biofilms associated with pgaB in MDR A. baumannii strains. The results also suggest to track its role in varying the pattern of drug resistance with further experimentation.